Gender and the (In)divisibility of Contested Sacred Places: The Case of Women for the Temple. Issue 4 (2nd May 2017) - Ben Shitrit, Lihi
Abstract: Contested sacred sites, over which different religious groups assert claims to exclusivity, have drawn scholarly attention to the spatial interaction between religion and politics. However, the gendered dimensions of inter-communal religious-political disputes over sacred space, and women's roles in these site-specific conflicts, have been largely neglected. Using a case study of Orthodox Jewish women's activism for access to Temple Mount al-Haram al-Sharif, this article demonstrates how attention to gender and to women's engagement in inter-communal conflict over sacred places can illuminate unique intra-communal processes that aim to make a contested sacred site increasingly indivisible for parties to the conflict.